Graphene-Based Metal-Organic Framework Hybrids for Applications in Catalysis, Environmental, and Energy Technologies - Jayaramulu, Kolleboyina; Mukherjee, Soumya; Morales, Dulce M; Dubal, Deepak P; Nanjundan, Ashok Kumar; Schneemann, Andreas; Masa, Justus; Kment, Stepan; Schuhmann, Wolfgang; Otyepka, Michal; Zbořil, Radek; Fischer, Roland A (Chemical reviews, 2022)
Current energy and environmental challenges demand the development and design of multifunctional porous materials with tunable properties for catalysis, water purification, and energy conversion and storage. Because of their amenability to de novo reticular chemistry, metal-organic frameworks (MOFs) have become key materials in this area. However, their usefulness is often limited by low chemical stability, conductivity and inappropriate pore sizes. Conductive two-dimensional (2D) materials with robust structural skeletons and/or functionalized surfaces can form stabilizing interactions with MOF components, enabling the fabrication of MOF nanocomposites with tunable pore characteristics. Graphene and its functional derivatives are the largest class of 2D materials and possess remarkable compositional versatility, structural diversity, and controllable surface chemistry. Here, we critically review current knowledge concerning the growth, structure, and properties of graphene derivatives, MOFs, and their graphene@MOF composites as well as the associated structure-property-performance relationships. Synthetic strategies for preparing graphene@MOF composites and tuning their properties are also comprehensively reviewed together with their applications in gas storage/separation, water purification, catalysis (organo-, electro-, and photocatalysis), and electrochemical energy storage and conversion. Current challenges in the development of graphene@MOF hybrids and their practical applications are addressed, revealing areas for future investigation. We hope that this review will inspire further exploration of new graphene@MOF hybrids for energy, electronic, biomedical, and photocatalysis applications as well as studies on previously unreported properties of known hybrids to reveal potential "diamonds in the rough".